2016
DOI: 10.1016/j.jcot.2016.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of near-infrared light on in vitro cellular ATP production of osteoblasts and fibroblasts and on fracture healing with intramedullary fixation

Abstract: The study demonstrated an immediate increase in ATP production and an initial acceleration of callus formation in the fracture healing process, in the presence of NIR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…Near-infrared light therapy was used to accelerate the healing of the left knee JOCD using a laser in the clinic and bulb for home use. Near-infrared light may accelerate the healing of bone injuries by stimulating osteoblasts [22]. Evidence is limited to animal studies, such as one animal study that found laser therapy improved signs of healing of osteochondral defects [23].…”
Section: Discussionmentioning
confidence: 99%
“…Near-infrared light therapy was used to accelerate the healing of the left knee JOCD using a laser in the clinic and bulb for home use. Near-infrared light may accelerate the healing of bone injuries by stimulating osteoblasts [22]. Evidence is limited to animal studies, such as one animal study that found laser therapy improved signs of healing of osteochondral defects [23].…”
Section: Discussionmentioning
confidence: 99%
“…At 2 or 3 weeks after fracture, the rats were anesthetized using sodium pentobarbital (40 mg/kg), radiographs were obtained in the anteroposterior orientation by high-resolution digital radiography using a DR 7500 system (Eastman Kodak Co., Rochester, United States) at an exposure of 45 kV for 5.5 s, and the femora were harvested. A radiographic healing score as described previously was assessed independently by 3 observers to grade the fracture healing [ 23 ]. The fracture healing was graded as follows: Grade 1, no calcification; Grade 2, patchy-calcification; Grade 3, calcification has the appearance of a callus; Grade 4, callus bridging across the fracture gap; Grade 5, continuity of bone trabeculae; Grade 6, remodeling to normal bone.…”
Section: Methodsmentioning
confidence: 99%
“…NIR-mediated reduction in IWL viscosity decreases the friction opposing ATP synthase rotation and results in ''smoother'' turning of the ATP synthase machinery. This theory is supported by the fact that cellular ATP level increases are immediate after PBM stimulation (Quirk et al, 2016), suggesting that the intracellular changes mediating elevated ATP production are alterations in physical properties rather than chemical processes, as the latter tends to occur with a slight time lag (Sommer, 2019). Yet another group suggested that the photo-absorbent metabolite pyropheophorbide-a (P-a) of dietary chlorophyl could facilitate light-driven energy production processes in animals (Xu et al, 2014).…”
Section: Cytochrome C 2+mentioning
confidence: 97%